2011
DOI: 10.1128/iai.00044-11
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Candida krusei and Murine Macrophages Results in Multiple Outcomes, Including Intracellular Survival and Escape from Killing

Abstract: Candida krusei is a fungal pathogen of interest for the scientific community for its intrinsic resistance to fluconazole. Little is known about the interaction of this yeast with host immune cells. In this work, we have characterized the outcome of the interaction between C. krusei and murine macrophages. Once C. krusei was internalized, we observed different phenomena. In a macrophage-like cell line, C. krusei survived in a significant number of macrophages and induced filamentation and macrophage explosion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Inhibition of macrophage cell division was previously reported for the fungal pathogens Cryptococcus neoformans , Candida krusei and C. albicans [21], [31], [32]. Here we found that in the presence of F. oxysporum , mitosis of macrophages was unsuccessful in approximately 25% of the cases.…”
Section: Discussionsupporting
confidence: 72%
“…Inhibition of macrophage cell division was previously reported for the fungal pathogens Cryptococcus neoformans , Candida krusei and C. albicans [21], [31], [32]. Here we found that in the presence of F. oxysporum , mitosis of macrophages was unsuccessful in approximately 25% of the cases.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, similar processes have been noted in C. albicans (Bain et al 2012) and C. krusei (García-Rodas et al 2011). It is likely that nonlytic escape offers a distinct advantage by minimizing proinflammatory signaling and thus ensuring that immune activity is kept to a minimal level.…”
Section: Cryptococcus Neoformans/gattiimentioning
confidence: 60%
“…Indeed, recently, C. albicans and C. krusei yeast cells have also been shown to escape via a nonlytic process first identified in Cryptococcus neoformans, in which both fungus and macrophage are left intact postexpulsion ( Fig. 2) (García-Rodas et al 2011;Bain et al 2012). …”
Section: Candida Speciesmentioning
confidence: 98%
“…These data are particularly interesting because C. krusei is one of the few non-albicans Candida spp. that are able to form filaments of any type; C. krusei forms pseudohyphae, not true hyphae, in macrophages (33). The ability of Candida species to trigger IL-1␤ production also corre- lated with their ability to induce macrophage lysis (data not shown).…”
Section: Fig 1 C Albicans-induced Macrophage Lysis Has Characteristimentioning
confidence: 79%